Strategi Penjualan Kerupuk Samiler Milernial dengan Aplikasi E-commerce - Pratiwi, Seli Septiana; Anzari, Prawinda Putri; Rozakiyah, Desy Santi (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2022)
Sales through e-commerce applications is commonly used by home industry, despite the lack of the progress and is dominated by business actors instead. E-commerce applications can expand product sales, in addition to promotions that are carried out without incurring costs. This service program aims to increase sales of Samiler cracker products through the application of e-commerce applications so that they can be reached by a wider range of consumers. Accordingly, observation was conducted to find out how to produce samiler cracker. Furthermore, interviews were also conducted to determine the ability of producers to utilize and manage information technology for business progress. In addition, assistance was provided in building market networks through the Shopee and Tokopedia applications, operationalizing e-commerce applications, and visualizing samiler crackers products. The results of the program show that the producers of samiler crackers understand and are able to operate e-commerce applications and develop market networks.